Satellite nighttime remote sensing promotes the spatially refined monitoring and assessment of offshore fishery - Hao Tian; Yang Liu; Jianchao Li; Qinwang Xing; He Sun; Yongjun Tian (International Journal of Digital Earth, 2024)
ABSTRACTOffshore small-scale fisheries, constituting 31% of global marine captures, are crucial for the promotion of sustainable fisheries. However, current fishery monitoring, assessments, and management remain incomplete. Nighttime remote sensing provides a critical perspective for monitoring fishery activities. Thus, in this study, a dynamic threshold fishing vessel detection (DTFVD) model was developed to assess and manage the spatiotemporal variations of offshore fisheries. Results demonstrated that the DTFVD model provides superior accuracy in nighttime fishery monitoring and can successfully identify a robust seasonal bimodal distribution of the Yellow-Bohai Sea's fisheries. By analysing the impacts of climate, environmental, and policy factors, this study reveals that ocean dynamics affect the seasonal and geographic distribution of offshore nighttime fisheries by enhancing ocean mixing and ecological processes. The effects of the COVID-19 lockdowns and Chinese summer fishing moratorium on offshore fisheries were also determined by nighttime remote sensing. According to future climate warming predictions, the habitats for the recruited migratory fish population may gradually move northward and disappear under climate risks, leading to the disappearance of suitable fishing areas for nighttime fisheries. Therefore, this study suggests integrating nighttime remote sensing into offshore fishery monitoring and assessment efforts for climate-adapted fishery management strategies.